Pengetahuan Ekologi Tradisional Masyarakat Orang Asli Jakun dalam Menilai Ekosistem Servis di Tasik Chini, Malaysia - Seftyono, Cahyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2011)
The relationship between human and ecosystem is inseparable from one another. Ecosystem management is also a reflection of human knowledge on the ecosystem itself. It is the knowledge structure that determines the pattern of relationship developed between man and environment in the surrounding ecosystem. Taking the example of the pattern of relations of community-environment as practiced by indigenous people in Tasik Chini, Malaysia, this paper shows how one of the good practice of traditional ecological knowledge is produced and reproduced by local people to be able to create a pattern of harmonious relations among citizens and between communities with its environment.